Cloning and characterization of a full-length CAB gene encoding the light harvesting chlorophyll a/b binding protein in Hevea brasiliensis - Kala R G; Jayashree R; Mathew Suni Annie; Supriya R; Thulaseedharan A (Rubber Science, 2017)
A full-length genomic DNA encoding the light harvesting chlorophyll a/b binding protein (CAB), expressed mainly in green leaves, for which the expression is reported to be directly related to the juvenility of the plant tissues, was cloned and sequenced. Initially CAB gene was amplified through PCR from the genomic as well as cDNA of Hevea brasiliensis using primers designed from the conserved regions of the CAB gene reported earlier from related plant species. The PCR amplified fragment (0.5 kb) was eluted, cloned adn sequenced. The sequence revealed the presence of 525 bps that showed 91 per cent homology with CAB mRNA from Ricinus communis. Further, full length CAB gene (0.8 kb) was amplified from genomic DNA using Ricinus communins specific primers. The sequence revealed the presence of a fragment of 802 bp which showed 90 per cent sequence homology with the reported cDNA sequence of CAB gene from Ricinus communis. The region amplified in the present study contains the full protein coding sequence with no introns. The phylogenetic tree showed the close relationship of the CAB gene of Hevea with Ricinus communins and Populus trichocarpa apart from the other eukaryotic plants. The aminoacid sequence deduced spans an open reading frame of 265 amino acids with predicted molecular weight of 28 kDA and iso-electric point (pl) as 5.45. A protein model was also predicted for the amino acid sequence. This is the first report on isolation and characterization of a full lenght CAB gene from Hevea brasiliensis.
Keywords: CAB gene; Characterization; Cloning; Differential expression